1995
DOI: 10.1088/0029-5515/35/12/i07
|View full text |Cite
|
Sign up to set email alerts
|

Alfven frequency modes at the edge of TFTR plasmas

Abstract: Portions of this document may be illegible in electronic image products. Images are produced from the best available original document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
13
1
6

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 14 publications
3
13
1
6
Order By: Relevance
“…25 Subsequent investigation, however, has shown that this peak is due to an edge-localized Alfvén mode, not a TAE. 26 The same mode often appears in Ohmic shots and, hence, is not a fast ion-driven mode. No additional loss of alpha particles was associated with this mode.…”
Section: Mhd and Collective Lossesmentioning
confidence: 98%
“…25 Subsequent investigation, however, has shown that this peak is due to an edge-localized Alfvén mode, not a TAE. 26 The same mode often appears in Ohmic shots and, hence, is not a fast ion-driven mode. No additional loss of alpha particles was associated with this mode.…”
Section: Mhd and Collective Lossesmentioning
confidence: 98%
“…45578.17063 Интерес к исследованию альфвеновских колебаний (АК) в токама-ках обусловлен прежде всего их способностью приводить к аномальным потерям энергичных частиц [1], что снижает эффективность нагрева плазмы и представляет потенциальную угрозу [2] для стенки камеры в больших термоядерных установках, в том числе в сооружаемом токамаке-реакторе ITER. Традиционно генерацию АК связывают с наличием в плазме термоядерных установок частиц высокой энергии, возникающих в результате применения дополнительного нагрева, в то же время АК наблюдаются и в режиме омического нагрева, в котором появление таких частиц маловероятно [2][3][4][5][6][7][8][9][10]. В последнем случае механизм генерации АК не вполне ясен и требует дальнейшего изучения.…”
unclassified
“…Обзор возможных типов АК в тороидальной геометрии можно найти в [2,3]. Попытки определения локализации АК в омическом режиме были предприняты в работах [4][5][6]. На токамаке TFTR было обнаружено, что АК локализованы на границе плазмы, в области r/a > 0.83 [4].…”
unclassified
See 2 more Smart Citations